PENGARUH PENGAWASAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PABRIK ( KASUS KARYAWAN BAGIAN PRODUKSI PT. PELITA AGUNG AGRINDUSTRI DI DURI) - Legawati, Kartika; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aims to menngetahui effect on employee productivity monitoring the production of PT. Pelita Agung Agrindustri Duri. Supervision as an independent variable (X) and labor productivity as the dependent variable (Y), and this study takes the number of respondents as many as 48 people. Data obtained through the questionnaire and then further processed to be tested through statistical analysis such as a simple regression analysis, t-test and correlation analysis and determination with the help of using SPSS version 17. results show that the results of t-test of hypothesis testing, (5.757)> (2,013 ). This ni indicates that engawasan signifikas effect on the level of employee productivity. The amount of supervision on employee productivity in the production of PT. Pelita Agung Agrindustri Thorn is at 41.9%.Keywords: Monitoring, Work Productivity, PT. Pelita Agung Agrindustri Duri.